2015
DOI: 10.2214/ajr.14.12786
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inversion Recovery Fat Suppression on Hepatic R2* Quantitation in Transfusional Siderosis

Abstract: OBJECTIVE The purpose of this study is to evaluate whether the application of spectral presaturation inversion recovery (SPIR) fat suppression in standard multiecho gradient-echo sequences has a significant effect on hepatic R2* quantitation in patients with iron overload syndromes. MATERIALS AND METHODS Eighty patients were scanned with a multiecho gradient-echo sequence without and with the application of SPIR. Six different postprocessing approaches were used to extract R2* values for maximum generality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
(35 reference statements)
0
16
0
Order By: Relevance
“…Both, CHESS and sSATs, pulses might affect the T2*/R2* estimation. Previous studies have shown an effect of fat suppression on the measured T2*/R2* values in patients with transfusional iron overload , which most likely arises from saturation of off‐resonant signal components within the broadened line profile associated with short T2* times. Similarly, the sSAT pulses also might impact the observed T2*/R2* values due to magnetization‐transfer effects through saturation of signal from protons bound to the broad macro‐molecular pool .…”
Section: Discussionmentioning
confidence: 99%
“…Both, CHESS and sSATs, pulses might affect the T2*/R2* estimation. Previous studies have shown an effect of fat suppression on the measured T2*/R2* values in patients with transfusional iron overload , which most likely arises from saturation of off‐resonant signal components within the broadened line profile associated with short T2* times. Similarly, the sSAT pulses also might impact the observed T2*/R2* values due to magnetization‐transfer effects through saturation of signal from protons bound to the broad macro‐molecular pool .…”
Section: Discussionmentioning
confidence: 99%
“…Third, the UTE‐A sequence uses fat suppression pulses to reduce streaking artifacts arising from the bright subcutaneous fat; otherwise, the streaking artifacts can distort the signal in the liver and cause R2* bias . Recent GRE studies have shown that application of fat suppression pulses in iron overloaded cases, even without fat, can lead to R2* underestimation . However, Krafft et al reported that there were only minor differences in R2* values due to application of fat suppression pulses in UTE imaging …”
Section: Discussionmentioning
confidence: 99%
“…11 Recent GRE studies have shown that application of fat suppression pulses in iron overloaded cases, even without fat, can lead to R2* underestimation. 17,24 However, Krafft et al reported that there were only minor differences in R2* values due to application of fat suppression pulses in UTE imaging. 11 Fourth, the optimal sequence among the five acquisition methods investigated was identified based on simulations only.…”
Section: Discussionmentioning
confidence: 99%
“…Another solution is to suppress the fat signal via inversion‐recovery or chemically selective fat saturation. However, recent studies show that these strategies can lead to R2* underestimation in cases of iron overload, even without fat . Another limitation of both concepts is that they do not consider the spectral complexity of fat, which comprises multiple lipid peaks …”
mentioning
confidence: 99%